Pengaruh Penggunaan Tepung Jagung dalam Pembuatan Silase Limbah Daun Singkong terhadap Perubahan Nutrisi, Kecernaan Bahan Kering, Protein Kasar dan Serat Kasar pada Kelinci Lokal - Riko Noviadi; Anjar Sofiana; Imelda Panjaitan (Politeknik Negeri Lampung., 2012)
An experiment was done at Cage Rabbit Trial and Laboratory of Animal Husbandry, Departement of Animal Husbandry, The State of Politechnic Lampung. The first experiment began in 10th until 30th July 2010. The second experiment began 27th August until 15 September 2010.The first experiment were conducted to know some treatments to made cassava leaf meal silage. The second experiment to know dry matter, crude protein, and crude fibre digestible on using of the cassava leaf meal silage in male local rabbit. The treatment and method two steps by used: In experiment 1, P1= 0% corn meeal, P2= 5% corn meal, P3= 10% corn meal, and P4=15% corn meal. In experiment 2, These used 16 male local rabbit. The rabbit were placed randomizely in battery cage. Parameter measured were : dry matter, crude protein , and crude fibre digestile. The nutrient digestibility determined by Harris (1983). The result of this experiment showed that ensilage processing increased quality of nutrien conten and its digestibility on local rabbit.. Keywords : Silage of cassava leaf meal, local rabbit, digestibility